EFFECTIVENESS OF BLENDED LEARNING STAGE ROTATION ON DIGITAL LITERACY AND CRITICAL THINKING - Haidar, Irajuana; Hidayati, Ully; Astiantih, Susi; Sanjani, Ade Riska (Universitas Sembilanbelas November Kolaka, 2025)
Rotation model on digital literacy and critical thinking skills among Mathematics Education students of the 2022 cohort at Sembilanbelas November University, Kolaka. With the increasing need for digital literacy and critical thinking skills in modern education, blended learning models such as Stage Rotation offer potential solutions to meet these demands in the technological era. A quasi-experimental method with a One Group Pretest-Posttest design was employed, involving a total sample of 15 students. Digital literacy and critical thinking skills were assessed using a likert scale questionnaire and essay test, respectively. The research instruments were validated to ensure reliability, and statistical analysis was conducted using a paired sample T-test to evaluate the effectiveness of the learning model. The results revealed a significant improvement in digital literacy and critical thinking skills following the intervention. These findings suggest that the blended learning model is an effective pedagogical strategy and has the potential to be implemented in curriculum courses. Further research is recommended to explore the impact of this model in other educational contexts to enhance the generalisability of the findings.